AN ANALYSIS OF BUSINESS MANAGEMENT STRATEGIES IN ZIMBABWE’S PARASTATALS, CHALLENGES AND SOLUTIONS: THE CASES OF THE GRAIN MARKETING BOARD AND ZIMBABWE NATIONAL WATER AUTHORITY - Mbambi, Titos; Maximilian, Chiunye Tonderai (International Journal For Research In Business, Management And Accounting, 2022)
The study sought to establish business management strategies in Zimbabwe’s parastatals, the challenges the parastatals face in the delivery of essential services, if any, and solutions to those challenges. The study was prompted by negative media reports on the parastatals and the complaints from stakeholders about the performance of the institutions. A case study was appropriate in this study because it enabled an exploration of the two parastatals in their real business settings. It also allowed the researchers to determine why good strategies are critical in businesses. The target population were 90 managers of the parastatals as well as 14 government officials who have a working relationship with these parastatals. A sample of 46 respondents was used to obtain data responses. Purposive sampling was most ideal in this study as the target was known and comprised of managers who had information on business management strategies, challenges and possible solutions. The government officials were directly and indirectly responsible for the selected parastatals. The major findings were that parastatals in Zimbabwe had adequate skilled and qualified manpower to administer them but largely lacked a succession plan due to political interference and also lacked the financial resources to carry out their operations and deliver quality products and/or services competitively. The major recommendations were that parastatals need to have a succession plan to ensure business continuity and adequate financial resources to be able to continue to discharge their mandates competitively.